The Role Of Qismu Al-Lughoh In Forming a Language Environment In a Modern Islamic Boarding School - Almuzakir Almuzakir; Wahyu Hanafi Putra; Lisma Meilia Wijayanti; Kunti Nadiyah Salma (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
This study aims to obtain clear and in-depth information about the role of Qismu al-lughoh through a language court to ensure the quality of foreign language skills for new male KMI students at Pondok Modern Arrisalah International Program Slahung Ponorogo. This study uses a descriptive research design combined with a case study approach. At the same time, the data collection techniques used are interview techniques, observation, and documentation. Data analysis techniques use content analysis by collecting data, reducing data, and drawing conclusions from research results. Based on the results of the study shows that the role of Qismu al-Lughah through language courts for new students includes providing routine vocabulary to increase students' knowledge of Arabic accompanied by daily speaking practice, creating an active language environment, supervision, and daily monitoring of the muhadatsah process through language investigators, giving punishment to offenders, holding language contests.